Characterization of duckweed and water hyacinth and their effect on the apparent digestibility in tilapia - Aroldo Botello-León; Yuniel Méndez-Martínez; Kirenia Pérez-Corría; Marcos Ortega-Ojeda; María Teresa-Viana; Charles Morán-Ribas (Revista MVZ Cordoba)
Objective. To evaluate the nutritional composition of duckweed (DW) (Lemna minor) and water hyacinth (WH) (Eichhornia crassipes) and its effect on the apparent digestibility of dry matter (%, ADDM), apparent digestibility of crude protein (%, ADCP) and the apparent digestibility of the crude lipid (%, ADCL) in the nutrition of tilapia (Oreochromis niloticus). Material and methods. The DW and WH were used to formulate nine isoproteic (32.47%), isolipidic (5.46%) and isoenergetic (16.45 MJ kg-1) diets, with three replicates and 15 male tilapia (36.36± 1.16 g) per repetition: 0% (T0); 10% (T10); 15% (T15); 20% (T20) and 25% (T25), respectively random. A principal component analysis (PCA) was applied. Results. The crude protein (%) of the WH and the DW, were 21.72% and 27.37% (p˂0.05), respectively. Fish fed with WH and DW, up to 10 and 15% inclusion in the diet, respectively, did not show significant differences (p>0.05) for ADDM. However, for ADCP and ADCL, up to 15 and 20%, respectively, significant differences (p>0.05) were not observed. Conclusions. Water hyacinth and duckweed meals were an alternative vegetable protein source, which can partially replace soybean meal and cornmeal in tilapia diets. The PCA suggests that the control diet, 10% WH, 10-15% DW, showed the best results in terms of the apparent digestibility of the nutrients.